Early Triassic-Early Jurassic Bivalve Diversity Dynamics - Ros Franch, Sonia (2012)
Bivalves are a highly diversified molluscan class, with a long history dating from early Cambrian times (Cope, 2000). Although the group already showed a steady diversification trend during the Paleozoic, it only became highly successful and expanded rapidly from the Mesozoic onward. The Triassic was, for bivalves, first a recovery period and later a biotic diversification event. It was also the time bivalves first fully exploited their evolutionary novelties.